Best Answer

-5n+9=-46

-5n+9-9=-46-9

-5n=-55

-5n/-5=-55/-5

n=11

Q: How do you solve -5n plus 9 equals -46?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

5n-2+2=4n 5n=4n n=0

5n+15 = 25 5n = 25-15 5n = 10 n = 2

5n + 15 = 25 you subtract 15 from both sides then you get 10 then divided 5n by 10 you get 2n

-3n+5n+4 = -4 2n = -4-4 2n = -8 n = -4

8n-2+4n = 66-5n 8n+4n+5n = 66+2 17n = 68 n = 4

Related questions

5n-2+2=4n 5n=4n n=0

5n+15 = 25 5n = 25-15 5n = 10 n = 2

5n + 15 = 25 you subtract 15 from both sides then you get 10 then divided 5n by 10 you get 2n

-3n+5n+4 = -4 2n = -4-4 2n = -8 n = -4

8n-2+4n = 66-5n 8n+4n+5n = 66+2 17n = 68 n = 4

Whatever your value of n is, you need to multiply it by 5 and then add 2 to get your answer. Below is how to solve it algebraically: 5n+2 = 0 (it needs to be equal to something in order to solve it, so I assumed that it equals zero) 5n = -2 n = -2/5

5n-25 = 10 5n = 10+25 5n = 35 n = 7

9-5n+1 = 15 -5n = 15-9-1 -5n = 5 Divide both sides of the equation by -5 to find the value of n: n = -5

5n+4 = -26 5n = -26-4 5n = -30 n = -6

it equals -4n

It is: 16n

6n